Pengaruh Faktor Faktor Fundamental terhadap Harga Saham Perusahaan Perbankan Syariah di Bursa Efek Indonesia Periode 2018-2020 (Triwulan) - Ganiar Firmansyah; Azib; Susilo Setiyawan (UNISBA Press, 2022)
Abstrack. This study aims to examine the effect of Fundamental Factors on stock prices. The object of research in this paper is a Sharia Banking Company and is listed on the Indonesia Stock Exchange in the period 2018-2020. The sample research technique was carried out using the purposive sampling method and obtained a research sample of 3 Islamic Banking Companies and listed on the Indonesia Stock Exchange in the period 2018-2020. The type of data used is secondary data in the form of financial reports and quarterly reports of the company. This study uses panel data regression analysis as a method to measure the effect of the independent variable on the dependent variable using the Eviews application. The panel data regression model was determined based on 3 tests, namely the Hausman Test Chow Test and Lagrange Multiplier Tests to obtain the best regression model. In this study, it was found that the best regression model for this study was the Random Effect Model (REM). After the panel data regression test the results show that simultaneously the fundamental variables ROA, EPS, CAR, and BOPO have a positive effect on stock prices of the Islamic banking sector listed on the Indonesia Stock Exchange in 2018-2020. Partially ROA, EPS, and BOPO have a significant effect while CAR has no significant effect on stock prices of the Islamic banking sector listed on the Indonesia Stock Exchange in 2018-2020. Abstrak. penelitian ini bertujuan untuk menguji pengaruh Faktor-Faktor Fundamental terhadap harga saham. Objek penelitian dalam penulisan ini adalah Perusahaan Perbankan Syariah dan terdaftar di Bursa Efek Indonesia pada kurun waktu 2018-2020. Teknik penelitian sampel dilakukan dengan menggunakan metode purposive sampling dan diperoleh sampel penelitian sebanyak 3 Perusahaan Perbankan Syariah dan terdaftar di Bursa Efek Indonesia pada kurun waktu 2018-2020. Jenis data yang digunakan ialah data sekunder berupa laporan keuangan dan laporan triwulanan perusahaan tersebut. Penelitian-ini menggunakan analisis regresi panel data sebagai metode untuk mengukur pengaruh variabel independen terhadap variabel dependen dengan menggunakan aplikasi Eviews. Model regresi data panel ditentukan berdasarkan 3 tes yaitu Uji Chow Uji Hausman dan Lagrange Multiplier Tests untuk mendapatkan model regresi terbaik. Dalam penelitian, ditemukan bahwa model regresi terbaik untuk penelitian ini merupakan Random Effect Model (REM). Setalah uji regresi data panel hasilnya menunjukkan bahwa secara simultan variabel fundamental ROA, EPS, CAR, dan BOPO berpengaruh positif terhadap harga saham sektor perbankan syariah yang terdaftar di Bursa Efek Indonesia pada ahun 2018-2020. Secara parsial ROA, EPS, dan BOPO berpengaruh signifikan sementara CAR tidak berpengaruh signifikan terhadap harga saham sektor perbankan syariah yang terdaftar di Bursa Efek Indonesia pada ahun 2018-2020 Abstrack This study aims to examine the effect of Fundamental Factors on stock prices. The object of research in this paper is a Sharia Banking Company and is listed on the Indonesia Stock Exchange in the period 2018-2020. The sample research technique was carried out using the purposive sampling method and obtained a research sample of 3 Islamic Banking Companies and listed on the Indonesia Stock Exchange in the period 2018-2020. The type of data used is secondary data in the form of financial reports and quarterly reports of the company. This study uses panel data regression analysis as a method to measure the effect of the independent variable on the dependent variable using the Eviews application. The panel data regression model was determined based on 3 tests, namely the Hausman Test Chow Test and Lagrange Multiplier Tests to obtain the best regression model. In this study, it was found that the best regression model for this study was the Random Effect Model (REM). After the panel data regression test the results show that simultaneously the fundamental variables ROA, EPS, CAR, and BOPO have a positive effect on stock prices of the Islamic banking sector listed on the Indonesia Stock Exchange in 2018-2020. Partially ROA, EPS, and BOPO have a significant effect while CAR has no significant effect on stock prices of the Islamic banking sector listed on the Indonesia Stock Exchange in 2018-2020